Violência e processos inclusivos em escolas de ensino fundamental anos finais-Boa Vista-RR - Pereira, Angelica de Almeida (2021)
The study presented starts from the first fruits with the social concern of violence suffered by children and adolescents, and the role of the school as an institution that promotes education through inclusive processes in the school context. The interface between violence at school and the environment of inclusive processes is connected, firstly, to situations of violence at school, then with the view of how the situations of violence experienced by students have an impact on inclusive processes at school, as it is in childhood they are knowledge is constructed, in the formation of concepts, relationships, assimilation of expressive affection ties in society. This is a case study, with a qualitative approach to highlight the problematization of the social phenomenon of violence in inclusive processes. The types of data collection were document analysis and interview through the focus group, using a semi-structured script. Data interpretation was performed from content analysis in order understand the situations of violence present in the school context with the inclusive processes of students in Elementary School Final Years of a public school in Boa Vista - RR, where the subjects were ninth grade students. Based on the systematization of records and data analysis, it was found that inclusion is considered as an aspect of socialization of the relationships established between thethe subjects, it goes beyond the curriculum established for learning, or the physical space that conceives them, and the limits or possibilities of the subjects, in this context, as well as the involvement among students and the welcoming motivation, manifesting itself in respect to difference and diversity and the very action among peers. In contrast, different situations of violence experienced or perceived by them are signaled, by the subjects, inside and outside the school space. Violent action is perceived from the invasion of the other's space, while at the same time reflects the importance of listening and intervention processes through conflict mediation. The violence experienced by students in other environments outside the school influences the school context. All are essential, teachers, students, coordination, educational guidance, psychological guidance, direction, employees, role of class leaders, and the family, together in the formation of the subjec to face violence and promote inclusive processes, rescuing the citinship, human dignity, making room for experimentation and new proposals for a social arrangements.